Carbon dioxide flow behaviour in macro-scale bituminous coal: An experimental determination of the influence of effective stress. (1st April 2023) - Zhang, Xiaogang; Jin, Chao; Zhang, Decheng; Zhang, Chengpeng; Ranjith, P.G.; Yuan, Yong
Abstract: Experimental studies on CO2 flow behaviour in coal are generally performed on meso-scale specimens (less than 100 mm in length), the results are not applicable at a larger scale. In this study, CO2 flow behaviours were experimentally tested on macro-scale reconstituted high rank coal samples (203 mm in diameter and 1 m in length). The permeability values, pressure development profiles, volumetric strains of the sample and the CO2 storage characteristics were recorded and compared to interpret the results. It was observed that CO2 permeability reduces with injection pressure, especially for supercritical CO2 injections but lower reduction rates were observed at higher CO2 injection pressures. With the increase of depth, CO2 permeability reduces and this reduction is greater for higher injection pressures. Maintaining a relatively high CO2 injection pressure creates greater pressure development in coal, and the effective zone of influence (areas where the CO2 pressure may remain at least 90% of the injection pressure) decreases with depth but increases with injection pressure to some extent. CO2 storage capacity reduces with depth, and the CO2 injection rate is greater for lower injection pressures during early stages of CO2 injection. However, the ultimate CO2 storage capacity increases with CO2 injection pressure for each injection. Graphical abstract: Image 1 Highlights: Coal permeability decreases with CO2 injection pressure and depth. Higher CO2 injection pressure produces greater pressure propagation in the sample. CO2 injection rate is greater for lower injection pressures at initial stage. CO2 storage capacity reduces with depth. The ultimate CO2 storage capacity increases with injection pressure.